Task Inhibition and Response Inhibition in Older vs. Younger Adults: A Diffusion Model Analysis - Schuch, Stefanie (Frontiers in Psychology, 2016)
Differences in inhibitory ability between older (64-79 years, N=24) and younger adults (18-26 years, N =24) were investigated using a diffusion model analysis. Participants performed a task-switching paradigm that allows assessing n-2 task repetition costs, reflecting inhibitory control on the level of tasks, as well as n-1 response-repetition costs, reflecting inhibitory control on the level of responses. N-2 task repetition costs were of similar size in both age groups. Diffusion model analysis revealed that for both younger and older adults, drift rate parameters were smaller in the inhibition condition relative to the control condition, consistent with the idea that persisting task inhibition slows down response selection. Moreover, there was preliminary evidence for task inhibition effects in threshold separation and non-decision time in the older, but not the younger adults, suggesting that older adults might apply different strategies when dealing with persisting task inhibition. N-1 response-repetition costs in mean RT tended to be larger in older than younger adults, but in mean error rates were larger in younger than older adults. Diffusion-model analysis revealed longer non-decision times in response repetitions than response switches in both age groups, consistent with the idea that motor processes take longer in response repetitions than response switches due to persisting response inhibition of a previously executed response. The data also revealed age-related differences in overall performance: Older adults responded more slowly and more accurately than young adults, which was reflected by a higher threshold separation parameter in diffusion model analysis. Moreover, older adults showed larger non-decision times and higher variability in non-decision time than young adults, possibly reflecting slower and more variable motor processes. In contrast, overall drift rate did not differ between older and younger adults. Taken together, diffusion model analysis revealed differences in overall performance between the age groups, as well as preliminary evidence for age differences in dealing with task inhibition, but no evidence for an inhibitory deficit in older age.